12 Glutaredoxin-overexpression attenuates chronic angiotensin-II induced hypertension and changes cardiac dynamics. (22nd March 2023) - Whyte, Hollie; Relan, Yashika; Murdoch, Colin
Abstract : Angiotensin-II (AngII) induces hypertension and cardiac hypertrophy and is a potent inductor of oxidative stress, which causes oxidative post-translational modifications (oxPTM). Glutaredoxin-1 (Glrx) catalyses the removal of an oxPTM, S-glutathionylation, and has been shown to be important in peripheral artery disease. Thereorfore, we investigated the effect of Glrx overexpression on ANGII-pressure overload. Glrx transgenic (TG) and wild-type (WT) littermates were implanted with osmotic pumps (Alzet) containing either saline or ANGII (1.1mg/kg/day; s.c). After 2 weeks, mice were anesthetised (2% isoflurane) and a pressure-volume (PV) catheter was inserted retrogradely into the left ventricle (LV). In WT mice, ANGII increased systolic and diastolic BP. However, no significant increase in SBP and DBP were observed in TG mice. Heart rates remained similar between all 4 groups. Although AngII increased BP in WT mice, LV end-diastolic/systolic pressure (EDP/ESP) and end systolic volume(ESV) remained unchanged between the four groups. However, ANGII significantly lowered end diastolic volume (EDV) in TG compared to WT. Hence, stroke volume (SV) was also lowered in TG compared to WT. Yet, these changes had no overall effect on LV cardiac output or stroke work. Interestingly, ANGII significantly lowered LV contractile state (Powermax) in response to ANGII in TG compared to WT mice. In summary chronic AngII infusion did not increase blood pressure in mice overexpressing Grx, but lowered pre-load with subsequent lower stroke volume and cardiac contractility. Future studies will investigate which redox sensitive proteins undergo reversal oxPTM to elicit these functional changes.